If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(2-x)=2x+7-7x+3
We simplify the equation to the form, which is simple to understand
5(2-x)=2x+7-7x+3
Reorder the terms in parentheses
+(+10-5x)=2x+7-7x+3
Remove unnecessary parentheses
+10-5x=+2x+7-7x+3
We move all terms containing x to the left and all other terms to the right.
-5x-2x+7x=+7+3-10
We simplify left and right side of the equation.
0x=0
0=0
This equation is an identity, so all real numbers are solutions.
| 6-7j=-2j+3 | | 4-3t=2t-20 | | 45x+9x=0 | | 43=7+y | | -4(4y-4)-y=-4(y-3) | | 7x^4-33x+26=0 | | 18(2-3)-2x=2x | | 6x+6=3(x+9) | | 2n+9=15 | | 4n+1=-23-2n | | g(x)=-f(-4) | | 3x-2y=-7 | | 6-7j=2j+3 | | 25W^2+10W+1=0 | | 5x+9=2(2x+3) | | -5x(4x-8y+4)= | | 3u+45=9(u+9) | | 2x^2+14x-144=0 | | -3x+5+6(x+1)=-2+3 | | 2(x+2)+4x=x+6 | | 9+c=-13 | | 4(s+2)-s=3(s+1) | | t=4n+4v | | 0.3(y+1)-0.4(3-2y)=0.2 | | 7x+5-4x-4=x | | (5cd^2)(-c^4d)= | | n^2+n+132=0 | | 2.5x+2.1=5.3 | | 5z^2-35=0 | | -4x^2+3x+10=0 | | 3u+45=9u+81 | | 3x-5=3(x+9) |